D-dimer Sebagai Indikator Prognostik Penderita Terkonfirmasi COVID -19 dengan Pneumonia Berat - Sonia Pradipta (Yayasan Pendidikan Medika Indonesia, 2023)
The novel coronavirus, designated SARS-CoV-2, has caused a global outbreak of respiratory illness termed coronavirus disease 2019 (Covid-19) since December 2019, and is still spreading quickly in more than 100 countries.1-3 There have been more than 600,000 patients with confirmed Covid-19 worldwide by the end of March 2020.3-5 One of the key issues has been the very high volume of patients presenting to health centers or hospitals during the outbreak. It clearly overwhelms the human and mechanistic capacities available, especially the need for critical care support. As such, risk stratification measures would clearly be helpful.5,6 Therefore, early and effective predictors of clinical outcomes are urgent needed for risk stratification of Covid-19 patients. D-dimer originates from the formation and lysis of cross-linked fibrin and reflects activation of coagulation and fibrinolysis. It has been reported that Covid-19 was associated with hemostatic abnormalities, and markedly elevated D-dimer levels were observed in those nonsurvivors.8 However, the prognosis value and the optimal cutoff value for D-dimer on admission to predict mortality have not been well evaluated